Visitors’ economic valuation of the attributes of marine resource conservation and management in the Perhentian Marine Park, Malaysia - Arabamiry, Seddigheh (2014)
East coast of Peninsular Malaysia is rich in marine biodiversity, and the only habitat for few and rare species of marine life. Perhentian Island Marine Park (PIMP) is located in Terengganu state. It is a popular marine park among Malaysia international tourists (64.28% in 2012). It seems that ecological attributes which are as variables in this study, are not in acceptable situation. For instance, coral cover in PIMP is in fair condition (32.8%). Underestimated non-market values of marine ecosystem can cause excessive depletion and the less conservation of these environmental goods in the process of development decisions. Therefore, in such studies, one of the most useful instruments to express the value of unique marine ecosystems like PIMP for decision maker is estimating the economic benefits (e.g. conservation or/and recreation) of PIMP. This study is aimed to estimate the economic values of ecological function and relevant management process that the visitors of PIMP held for them (e.g. PIMP visitors’ willingness to pay and Marginal Rate of Substitution of attributes) by applying choice modelling method of stated preference techniques. Cochran’s formula in which population size is assumed last year visitors of PIMP (2012), was employed to estimate sample size; therefore the total collected data consist of 380 Questionnaires which have been completed by visitors through a face-to-face interview in two main islands: Perhentian Besar and Perhentian Kecil. Several models including Multinomial Logit (MNL) and Mixed Logit (ML) models for each part of the study have been estimated. The results infer that the visitors of PIMP are aware of the sensitivity of the main marine resources and the respondents’ intention to improve its status. Based on estimated models, the greatest visitors’ preference for different attribute levels in part one with RM38.9 was for water quality improvement from status quo to 5%. As well, the next marginal value in this part was for coral cover improvement from status quo to 5% with RM30.7. Similar marginal rate of substitutions (MRS) for part two was for management, relative to water quality with RM109.5 for improvement from status quo to level 1 and next amount was related to fish species management for improvement from status quo to level 1 with RM68.6. Economic valuation is a procedure to identify and quantify the major benefits which are available by marine Park as environmental goods. Thus, the results of this study as an economic valuation provide invaluable support for conservation efforts in the direction of maintenance biodiversity conservation. The benefits of Marine Park for society via Marginal Rate of Substitution could encourage policy makers. Meanwhile, the profile of respondents and their perceptions will be useful to assists all stakeholders in their future management and development plans in Marine Park sites in Malaysia and similar case in South East Asia. Budget, aims of the study, and lack of reliable and available information due to being a more or less new phase regarding CM technique, may create some limitation in this study. Hence, in order filling gaps, inclusion users and non-users of PIMP as unit of sample in CM technique for future economic valuation studies through zoning plan is suggested.